KLASIFIKASI KEMAMPUAN LAHAN UNTUK PEMBANGUNAN DI WILAYAH DAERAH ALIRAN SUNGAI MANIKIN BAKI, PROVINSI NUSA TENGGARA TIMUR - Yofris Puay (Partner, 2020)
The study was conducted to determine the land capability class in the Manikin Baki watershed, identify limiting and potential factors on the land and determine the actions taken to overcome existing limiting factors for sustainable land use. The method used is matching to 9 factors that are potential and limiting.The results showed that the Land Capability Class in Manikin Baki watershed was dominated by land capability class III with 55.77% of the total research location. The main factor that is limiting is the slope. Conservation action that needs to be done in order to overcome the limiting factors is to carry out heavy conservation in the form of making terraces. Key Words: land cappability, resources, Manikin Baki waterdhrd